Rib hump deformity assessment using the rib index in adolescent idiopathic scoliotics treated with full screw or hybrid constructs: aetiological implications. Issue 2 (December 2015) - Soultanis, Konstantinos; Stavropoulos, Nikolaos; Grivas, Theodoros; Tsiavos, Konstantinos; Starantzis, Konstantinos; Papagelopoulos, Panayiotis
Abstract Background Review of literature reveals that in Idiopathic Scoliosis (IS) children, the post-operative rib hump (RH) correction using full transpedicular screw construct has never been compared to hybrid constructs, applying the Rib-Index (RI) method. Therefore the aim of this report is to study which of the above two constructs offers better postoperative Rib Hump Deformity (RHD) correction. Methods Twenty five patients with Adolescent Idiopathic Scoliosis (AIS) were operated using full pedicle screw construct or hybrid construct. Sixteen underwent full screw instrumentation (group A) and nine an hybrid one (group B). The median age for group A was 15 years and for group B 17.2 years. The RHD was assessed on the lateral spinal radiographs using the RI. The RI was calculated by the ratio of spine distances d1/d2, where d1 is the distance between the most extended point of the most extending rib contour and the posterior margin of the corresponding vertebra on the lateral scoliosis films and d2 is the distance from the least projected rib contour and the posterior margin of the same vertebra. Moreover the amount of RI correction was calculated by subtracting the post-operative RI from the pre-operative RI. Results Although within group A the RI correction was statistical significant (the pre-op RI was 1.93 and the post-op 1.37; p<0.001) and similarly in group B (the mean pre-op RI was 2.06 while the mean post-op 1.51; p=0.008), between group A and B the post-operative RI correction mean values were found to be no statistically significant, (p=0.803). Conclusion Although the pre- and post-operative RI correction was statistically significant within each group, this did not happen post-operatively between the two groups. It appears that the RHD correction is not different, no matter what the spinal construct type was used. Provided that the full screw construct is powerful, the post-operative derotation and RHD correction was expected to be better than when an hybrid construct is applied, which is not the case in this study. It is therefore implied that the RHD results more likely from the asymmetric rib growth rather than from vertebral rotation, as it has been widely believed up to now. In 2013 Lykissas et al, reported that costoplasty combined with pedicle screws and vertebral derotation significantly improved RH deformity as opposed to pedicle screws and vertebral derotation alone. Another interesting implication is that the spinal deformity is the result of the thoracic asymmetry, implication in line with the late Prof. John Sevastikoglou's (Sevastik's) thoracospinal concept.